2018
DOI: 10.1155/2018/4591729
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Total Bilirubin Level Is Associated with Poor Outcomes in Pediatric Patients with Sepsis-Associated Liver Injury

Abstract: Aims The aim of this study was to assess the prognostic value of the serum total bilirubin (TBIL) level in pediatric patients with sepsis-associated liver injury (SALI). Methods We performed a retrospective study of patients with SALI admitted to the pediatric intensive care unit (PICU) in Shanghai Children's Hospital between December 2012 and December 2015. Serum TBIL concentration was determined within 72 h after PICU admission. Results Seventy-two patients with SALI were included in this study. The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Liver injury is a common risk factor for poor mortality in patients with sepsis. 20 The incidence rate of sepsis-associated ALI in patients enrolled in this study during a 1-year period was 12.2% (10/82), which is consistent with our previous retrospective study on the sepsis-associated ALI incidence rate (9.7%, 72/745) 21 ; however, the incidence rate observed in the current study was lower than that of a recent study conducted in Southwest China (19.6%). 3 The PICU mortality of patients with sepsis-associated ALI was 40% in the present study, which is consistent with the observation of our previous retrospective study (36.1 [26/72]).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Liver injury is a common risk factor for poor mortality in patients with sepsis. 20 The incidence rate of sepsis-associated ALI in patients enrolled in this study during a 1-year period was 12.2% (10/82), which is consistent with our previous retrospective study on the sepsis-associated ALI incidence rate (9.7%, 72/745) 21 ; however, the incidence rate observed in the current study was lower than that of a recent study conducted in Southwest China (19.6%). 3 The PICU mortality of patients with sepsis-associated ALI was 40% in the present study, which is consistent with the observation of our previous retrospective study (36.1 [26/72]).…”
Section: Discussionsupporting
confidence: 90%
“…3 The PICU mortality of patients with sepsis-associated ALI was 40% in the present study, which is consistent with the observation of our previous retrospective study (36.1 [26/72]). 21 The mortality rate was significantly higher in patients with sepsis-associated ALI (40%, 4/10) than in patients without ALI (12.5%, 9/72) in our present study. Therefore, early identification of liver injury during sepsis needs more clinical and research attention and will be helpful for developing strategies for improving the outcome of sepsis.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In addition, we also found that TBIL was signi cantly different in sepsis compared with infection or healthy controls, and showed certain diagnostic value. Given that hyperbilirubinemia is a common complication of sepsis, it is used as an indicator of liver function in APA CHEII and sequential organ failure scores (8), which is associated with poor prognosis of sepsis -associated liver injury (25). Some studies also believe that although TBIL is higher in the sepsis group, its correlation is not clinically signi cant because it is a parameter of the SOPA standard (26).…”
Section: Discussionmentioning
confidence: 99%
“…Gupta, T et al demonstrated that elevated hepatic SOFA scores were most predictive of in-hospital death [21] . In addition, serum T-BIL level lactate level, lactate clearance rate, increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST), and decreased C3 and C4 were all independent risk factors for the prognosis of liver injury [22][23][24][25] . However, there is still a lack of cohort studies with large samples, and there are few studies on the long-term prognosis of SALI [26] .…”
Section: Introductionmentioning
confidence: 99%